Re-examining the Effect of Volatility Persistence on Nigerian Stock Market Returns: Mean-Revert Garch Approach: Array - Bello, Abdullahi Ibrahim (The Journal of Accounting and Management, 2020)
The investment decision in the Nigerian stock is based on the level of volatility of the market. However, the volatility persistence of stock returns in the Nigerian market has negatively affects the participation of investors in the market. This study re-examined the effect of persistent volatility on the prices of the stocks in the Nigerian market between 2008 and 2018. With the use of ARCH and GARCH estimations, the study revealed three distributional assumptions with the co-efficients as (0.897, 0.939 and 0.956) revealing that the returns exhibit high volatility persistence at different selection criterion models. It concludes therefore, that the Nigerian stock market exhibits high volatility persistence. Hence, the study recommends that the regulators in the Nigerian stock market should model the regulatory framework guiding the operations in line with emerging markets with less volatile stock returns.